Analysis of tweet form's effect on users' engagement on Twitter - Xu Han; Xingyu Gu; Shuai Peng (Cogent Business & Management, 2019)
This research focuses on the effects on users' engagement of different tweet forms including text length, text sentiment and the usage of hashtag, mention, video or picture URL. In the first part, we analyze the tweets of five companies from the apparel industry and finds out that there is no universal form that can boost user's engagement, but in company scale, the effects of different forms between companies are various due to company attributes. Hence, in our second research, we expand the dataset and analyze the formats of tweets from 70 brands focusing on the attribute of the industry section. The conclusion shows that industries such as luxury and hardware technology are more digital sensitive and benefit more using more hashtag and video or picture URL while industry such as software industry is more digital insensitive. The result could provide evidence and guidance for different categories of companies to design tweets with high customer engagements and serve as a reference for enterprises on other media platforms.
Keywords: 650; social media marketing; Twitter; Tweet Form; user engagement